MASYARAKAT SIPIROK DI TAPAK KUDA DESA GUNUNG SERAWAN KAB. SIMALUNGUN (1956-1990) - nababan, erni friska luciana (Trombo, 2013)
Sipirok’s Society in Tapak Kuda Gunung Serawan’s Village Simalungun’s Regency in year 1956-1990 is the title of my minithesis. In this writing, i use the common of history’s method, that is heuristic, resource critic, interpretation and historiography. In heuristic’s method, the resource of Sipirok’s society is gotten from collection of writing resource and it use of research field pass through interview. Resource critic is a stage which used to get a data and the data-validity can be valued of the objectively by internal and external critic. Interpretation is method in stage of looking for the data-validity that used analysis’s method, after analyzing wiil be born a result objectively and natural from the object research. The next stage is historiography that arranging scientific work in order to create a interesting narrative or scientific knowledge and the last become a history’s writing. The moving out of Sipirok’s society from Tapanuli Selatan to Tapak Kuda can be said like a moving out to change of destiny (migration). The purpose of moving out or migration in common to get the fertile area and to apply the economic development. Because economic’s factor is very strong to influence human to move out or migrate to other place. Theoretically, economic’s growth in a certain region or area will be followed with a basic alterations in all aspect of human life. The moving out or migration of the inhabitant it is not just only because of economic’s factor but also there are many other factor which all of them purpose in order to change life better. It’s not close possible that almost of people have ever done to move out as an effort to develop the life quality of their selves. Like that with the Sipirok’s society in Tapanuli Selatan where the main motive of the moving out from their source area, Tapanuli Selatan, to Tapak Kuda is cause of decrease quality of the human resource then be followed by the natural resource declined as a pillar of their life. Beside of the factor, the other factor is a wanting of Toungku Mariman Harahap to develop a special village for Sipirok’s society that have a Harahap’s clan. The process shape of Tapak Kuda becomes a village, the first is opened by someone who come from Tapanuli Selatan, He was Toungku Mariman Harahap. Sipirok’s society started to move out from Tapanuli Selatan to Tapak Kuda in 1956. The natural condition of Tapak Kuda in common is fertile’s land, that is too good to be a field of agricultur.